2023
DOI: 10.1111/aogs.14713
|View full text |Cite
|
Sign up to set email alerts
|

Maternal age and the risk of fetal aneuploidy: A nationwide cohort study of more than 500 000 singleton pregnancies in Denmark from 2008 to 2017

Line Elmerdahl Frederiksen,
Sofie Møller Ølgaard,
Laura Roos
et al.

Abstract: IntroductionIn this register‐based study of pregnancies in Denmark, we assessed the associations between maternal age and the risk of fetal aneuploidies (trisomy 21, trisomy 18, trisomy 13, triploidy, monosomy X and other sex chromosome aberrations). Additionally, we aimed to disentangle the maternal age‐related effect on fetal aneuploidies by cases with translocation trisomies and mosaicisms.Material and methodsWe followed a nationwide cohort of 542 375 singleton‐pregnant women attending first trimester scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Furthermore, studies had indicated that the incidence of fetal chromosomal aneuploidy was higher in women over 35 years of age [5,21,25] . Most researchers believed that it was mainly due to the occurrence of premature separation of sister chromatids, non-disjunction in meiosis II, and reverse segregation during the development of oocytes in older women, which can signi cantly increase the incidence of trisomy in fetal tissue chromosome [26,27] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies had indicated that the incidence of fetal chromosomal aneuploidy was higher in women over 35 years of age [5,21,25] . Most researchers believed that it was mainly due to the occurrence of premature separation of sister chromatids, non-disjunction in meiosis II, and reverse segregation during the development of oocytes in older women, which can signi cantly increase the incidence of trisomy in fetal tissue chromosome [26,27] .…”
Section: Discussionmentioning
confidence: 99%
“…Although insignificant, several reasons may provide an explanation. First, the proportion of pregnancies with advanced maternal age, a well-established risk factor of chromosomal abnormalities in the offspring [ 34 ], almost doubled after the termination of the One-Child Policy [ 35 ]. Second, new genetic techniques promote the detection and correct categorization of chromosomal issues [ 36 ].…”
Section: Discussionmentioning
confidence: 99%